Diagnosis of Catecholaminergic Polymorphic Ventricular Tachycardia - Ekaterina K. Kulbachinskaya; Vera V. Bereznitskaya (Вопросы современной педиатрии, 2024)
Catecholaminergic polymorphic ventricular tachycardia (CPVT) is primary electrical heart disease characterized by development of polymorphic, including bidirectional, ventricular tachycardia in response to adrenergic stimulation caused by physical or emotional stress. The major CPVT’s clinical manifestation is faintness caused by exercises, emotional stress, or beta-adrenergic agonists administration. This disease has high mortality rate without any treatment. The difficulties of preclinical diagnosis as well as late diagnosis after CPVT’s clinical signs manifestation dictate the need to analyze and systematize all the data on disease’s causes, clinical manifestations, and existing diagnostic approaches. This work has particular focus on the analysis of the disease molecular genetic causes and the spectrum of associated disorders in patients with CPVT regarding its diagnosis, management, and prognosis. Future research topics were determined for improving diagnosis quality and reducing mortality of patients with CPVT.